Rural and remote health care: the case for spatial justice - Karen Hayes; Kristy Coxon; Rosalind Bye (Rural and Remote Health)
Almost universally, people living in rural and remote places die younger, poorer, and sicker than urban-dwelling citizens of the same country. Despite clear need, health services are commonly less available, and more costly and challenging to access, for rural and remote people. Rural geography is commonly cited as a reason for these disparities, that is, rural people are said to live in places too distant, too underpopulated, and too difficult to access. However, all these descriptions tacitly compare rural places with urban spaces. That is, rural places are perceived as too distant from cities, less populated than cities, and too difficult to access from cities. This relative framing situates urban geography as normal, and non-urban geography as abnormal and blames people who live outside of normalised urban spaces for their own disadvantage. It suggests rural people should expect less service, higher costs, and increased awkwardness in using healthcare services due to the 'abnormality' of living in rural spaces. The concept of spatial justice provides an alternative way of considering geography that we propose could effectively reframe understanding of and approaches to rural and remote health care to improve health outcomes.